A case report of gastrointestinal bleeding during dual antiplatelet therapy in a patient with coronary heart disease - E. S. Deeva; M. A. Isaikina; O. Iu. Trushina; V. V. Fomin; A. V. Pogonin; M. K. Tamkaeva (Евразийский Кардиологический Журнал, 2024)
Cardiovascular disease continues to be the leading cause of death in both developed and developing countries. Low-dose acetylsalicylic acid is used worldwide for primary and secondary prevention of cardiovascular events on a long-term basis to reduce mortality and lethality. At the same time, the incidence of gastrointestinal bleeding associated with acetylsalicylic acid intake is steadily increasing. The presented case report illustrates the development of gastrointestinal bleeding against the background of dual antiplatelet therapy in a patient with coronary heart disease with a history of ulcers. A 65-year-old patient with an aggravated coronary history was routinely hospitalized in the cardiology department. On admission to the hospital, taking into account the increasing complaints of crushing pain behind the sternum, acute coronary syndrome was excluded in the patient, esophagogastroduodenoscopy was performed, which revealed a subcardia callous ulcer. On the same day, there was a negative trend in clinical manifestations in the form of syncope, hypotension up to 70/50 mmHg, vomiting «coffee grounds». According to the data of repeated emergency esophagogastroduodenoscopy a superficial ulcerous defect in the subcardia area with bleeding vessel in the bottom was revealed and combined endoscopic hemostasis was performed. Further examination of the patient revealed Helicobacter pylori infection, which in combination with other risk factors influenced the occurrence of this complication. First-line anti-ulcer eradication therapy was prescribed. The patient subjectively evaluated his condition as satisfactory and was discharged with recommendations for outpatient treatment. The purpose of this case report is to emphasize the importance of timely detection and treatment of gastrointestinal diseases in high-risk patients. This may allow for timely prevention of bleeding in patients with high-risk coronary heart disease in the future, taking into account a personalized approach.